Cryoballoon Ablation Strategy in Persistent Atrial Fibrillation - Straube, Florian; Pongratz, Janis; Kosmalla, Alexander; Brueck, Benedikt; Riess, Lukas; Hartl, Stefan; Tesche, Christian; Ebersberger, Ullrich; Wankerl, Michael; Dorwarth, Uwe; Hoffmann, Ellen (Frontiers in Cardiovascular Medicine, 2021)
Background Cryoballoon ablation (CBA) is established for pulmonary vein isolation (PVI) in paroxysmal atrial fibrillation (AF). The objective was to evaluate CBA strategy in consecutive persistent AF patients in the initial AF ablation procedure. Material and Methods Prospectively, symptomatic persistent AF patients scheduled for AF ablation all underwent cryoballoon PVI. Technical enhancements, lab management, safety, single-procedure outcome, predictors of recurrences, and durability of PVI were evaluated. Results From 2007 to 2020, a total of 1,140 persistent AF patients, median age 68 years, underwent CBA. Median left atrial diameter (LA) was 45 mm (IQR 8), and CHA2DS2-VASc-Score 3 (2). Acute isolation was achieved in 99.6% of the pulmonary veins by CBA. Median LA time and median dose area product decreased significantly over time (p<0.001). Major complications occurred in 17 (1.5%) patients including 2 (0.2%) Stroke/TIA, 1 (0.1%) tamponade, relevant groin complications, 1 (0.1%) significant ASD, and 4 (0.4%) persistent phrenic nerve palsy (PNP). Transient PNP occurred in 66 (5.5%). No atrio-esophageal fistula was documented. Five deaths (0.4%), unrelated to the procedure, occurred very late during follow-up. After initial CBA, arrhythmia recurrences occurred in 46.6% of patients. Freedom from atrial arrhythmias at 1-, and 2-year was 81.8%, and 61.7%, respectively. Independent predictors of recurrence were LA diameter, female sex, and the use of the first cryoballoon generation. Repeat ablations due to recurrences were performed in 268/1,140 (23.5%) of patients. No PV reconduction was found in 49.6% of patients, and 73.5% of PVs. This rate increased to 66.4% of patients, and 88% of PVs if an advanced cryoballoon was used in the first AF ablation procedure. Conclusion CBA in symptomatic persistent AF is a reasonable strategy in the initial AF ablation procedure.